Iron induces blood-brain barrier alteration contributing to cognitive impairment in β-thalassaemia mice - Parinda Jamrus; Nuttanan Pholngam; Benjaporn Kiatpakdee; Kittikun Viwatpinyo; Jim Vadolas; Sukonthar Ngampramuan; Saovaros Svasti; Pornthip Chaichompoo (Scientific Reports)
Abstract Iron overload has been associated with cerebrovascular disease and cognitive impairment in β-thalassaemia patients, typically appearing earlier than in the general population. However, the mechanisms of iron overload on cerebrovascular pathology remain unclear. This study investigated the effects of heavy iron overload on the blood-brain barrier and neurohistology, particularly in the CA3 region of hippocampus and its contribution to cognitive impairment in β-thalassaemia mice. Three-month-old female β-thalassaemia and wild-type mice received iron dextran via intraperitoneal injection to induce heavy iron overload. While β-thalassaemia mice with low baseline iron show cognitive impairment at 22 months, equivalent to 70–80 human years, heavy iron overload accelerated cognitive decline, leading to impaired spatial learning and memory by 12 months, equivalent to 35–40 human years, in both β-thalassaemia and wild-type mice. Iron-loaded mice have reduced hippocampal CA3 pyramidal neurons and significant iron accumulation in blood vessels, with no increase in neuronal iron levels. A significant decrease in ZO-1, a tight junction protein, indicated decreased blood-brain barrier integrity and potential iron leakage into the brain. While iron-loading had no effect on astrocytes, elevated Iba1 expression in microglia suggests microglia activation as a protective response. However, persistent iron overload may lead to chronic neuroinflammation, neurodegeneration, and cognitive decline. These results underscore the critical role of iron overload in accelerating cognitive decline in β-thalassaemia and suggest that regular monitoring of iron levels and chelation therapy may help prevent early cognitive impairment, ultimately improving the quality of life for β-thalassaemia patients.